Formas de recriação do mito em contos de Mia Couto - Ferreirinha, Carlos Augusto dos Santos (2017)
The aim of this assignment is to reflect on the ways of recreating Afro-Mozambican myths in the narratives “A Lenda de Namarói” (2012), “A infinita fiandeira” (2009) e “Nas águas do tempo” (2012), by Mia Couto. The problematization questions: to what extent do the African Myths imply the process of identify and social institution of the African community and, by extension, of the Mozabican? How does Mia Couto assimilates these mythical aesthetics in his narratives? Two hypotheses were selected: The Myth inscribes an affirmation in the construction and institutionalization of life and in the Regime of Truth of the Afro-Mozambican people; Mia Couto's narrative recovers and recreates the aesthetic and the mythic structures of Mozambican culture in order to keep alive the veracity and the belief in the Myths as a matrix of real and valid thought. As a theoretical basis for approaching the Myth, we highlight the concepts of Anti-Narcissus, Penser autrement (CASTRO,2015), Regime of Truth (FOUCAULT,1999); and Tautegory (SCHELLING, 2007); in relation with the process of mythical aesthetics recreation in the literary composition, we utilize the concept of transcreation, by Haroldo de Campos (1992), as well as semiotic sign propositions of Charles Sanders Peirce (2000) and Octavio Paz (1976). It is observed that Mia Couto retrieves and presentifies mythical aesthetic and structural compositions as a way of institutionalizing and giving voice to orality, to the matix of thought and to the Regime of Truth of the Afro-Mozambican subject as a living and present reality